Energy-efficient management modeling towards interior thermal comfort: an architectural element manipulating case study on small detached houses in Bangkok - Nuchnapang Keonil; Nopadon Sahachaisaeree (My University, 2010)
This paper investigates the thermal perceptual aspect from daily activities. The research uses the cases of small detached houses in Bangkok to examine the best manipulation of architectural elements to optimally provide thermal comfort in the Thai living context applying a multi-facet research methodology. Two aspects of design manipulation—the spatial arrangements and buildings feature—are examined towards the optimization modeling. The level of perceived comfort obtained from data analysis is used as input in the modeling program to be tested to obtain the model of comfort optimization strategy and to set the guideline of passive design for tropical climate.
Keywords: Building Energy and Comfort Optimization